2020
DOI: 10.1007/s00406-020-01164-5
|View full text |Cite
|
Sign up to set email alerts
|

Combined antisaccade task and transcranial direct current stimulation to increase response inhibition in binge eating disorder

Abstract: Binge eating disorder (BED) is associated with deficient response inhibition. Malfunctioning response inhibition is linked to hypoactivation of the dorsolateral prefrontal cortex (dlPFC), where excitability could be increased by anodal transcranial direct current stimulation (tDCS). Response inhibition can be assessed using an antisaccade task which requires supressing a dominant response (i.e. saccade) towards a newly appearing picture in the visual field. We performed a double-blind, randomised, placebo-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 52 publications
1
54
0
Order By: Relevance
“…Six studies were identified as directly targeting the brain for the treatment of impulsivity symptoms in people with binge eating behaviour. More specifically, one study used neurofeedback [44] whereas five studies investigated the effectiveness of non-invasive brain stimulation methods comparing verum with sham stimulation [40][41][42][43]45].…”
Section: Interventions Using a Direct Neuromodulation Approachmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies were identified as directly targeting the brain for the treatment of impulsivity symptoms in people with binge eating behaviour. More specifically, one study used neurofeedback [44] whereas five studies investigated the effectiveness of non-invasive brain stimulation methods comparing verum with sham stimulation [40][41][42][43]45].…”
Section: Interventions Using a Direct Neuromodulation Approachmentioning
confidence: 99%
“…However, Gay and colleagues [41] did not find a reduction after verum or sham rTMS (10 Hz) over the left DLPFC even after 10 stimulation sessions in terms of binging and purging episodes. Furthermore, there were three studies administering transcranial direct current stimulation (tDCS) [40,42,43]. Burgess and colleagues [40] showed decreased inlab food intake and food craving in patients with BED, and decreased urge to binge eat, particularly in men, following anodal verum tDCS administration (2 mA) over the right DLPFC in comparison to sham stimulation.…”
Section: Interventions Using a Direct Neuromodulation Approachmentioning
confidence: 99%
See 3 more Smart Citations